Трансцендентная «женственность» Валерня Брюсова и ее демонический эротизм - Panek, Inna (Rusycystyczne Studia Literaturoznawcze, 2015)
The author of this article attempts to describe and explain the status and role of the female characters in poetry and life of an “older” symbolist, Valery Bryusov. The mythological origins of women in his works are to underline that the poet draws on the classical literature. The mythological characters, functioning in the Western societies as cultural models, play similar role and the poet takes them as his point of departure to present the symbolist perspective on women. Moreover, Bryusov follows the ideas of free, and at the same time scandalous, French symbolism, which he tried to introduce into the Russian social and artistic life.